Intravenous Administration of Glial Cell Line-Derived Neurotrophic Factor Gene-Modified Human Mesenchymal Stem Cells Protects Against Injury in a Cerebral Ischemia Model in the Adult Rat - Horita, Yoshifumi (2006)
Intravenous administration of human mesenchymal stem cells (hMSCs) prepared from adult bone marrow has been reported to ameliorate functional deficits after cerebral artery occlusion in rats. Several hypotheses to account for these therapeutic effects have been suggested, and current thinking is that neuroprotection rather than neurogenesis is responsible. To enhance the therapeutic benefits of hMSCs potentially, we transfected hMSCs with the glial cell line-derived neurotrophic factor (GDNF) gene using a fiber-mutant F/RGD adenovirus vector and investigated whether GDNF gene-modified hMSCs (GDNF-hMSCs) could contribute to functional recovery in a rat permanent middle cerebral artery occlusion (MCAO) model. We induced MCAO by using intraluminal vascular occlusion, and GDNF-hMSCs were intravenously infused into the rats 3 hr later. MRI and behavioral analyses revealed that rats receiving GDNF-hMSCs or hMSCs exhibited increased recovery from ischemia compared with the control group, but the effect was greater in the GDNF-hMSC group. Thus, these results suggest that intravenous administration of hMSCs transfected with the GDNF gene using a fiber-mutant adenovirus vector may be useful in the cerebral ischemia and may represent a new strategy for the treatment of stroke.